Math
posted by Sharon .
How do I know if the points (2,15) lie on a parabola which has the equation y=x^26x7?

Math 
Henry
(2,15), Y = X^2  6X 7.
When 2 is plugged into the equation,
you should get Y = 15 which proves that the point is on the parabola.
Y = 2^2  6 (2) 7 = 15
Respond to this Question
Similar Questions

math
(4,2) and (2,8) lie on the line Ax2By = 28. What is the value of A? 
math
A parabola has the equation y = 4(x3)^27 Choose 2 true statements: A) The parabola has a minimum value B) The parabola has a maximum value C) The parabola does not cross the yaxis D) The parabola does not cross the xaxis E) The … 
math
A parabola has the equation y = 4(x3)^27 Choose 2 true statements: A) The parabola has a minimum value B) The parabola has a maximum value C) The parabola does not cross the yaxis D) The parabola does not cross the xaxis E) The … 
MATHS
a parabola passes through the points (1,1) , (2,0) and (3,1) the equation of the parabola is y=ax^2 + bx + c a) write down a system of equations representing this parabola. b) solve the corresponding system and hence write down the … 
math
the points (9,0) and (19,0) lie on parabola. a.) determine an equation for its axis of symmetry: X=5 b.) the ycoordinate of the vertex is 28. determine an equation for the parabola in factored form. c.)write your equation in part … 
pre cal
What is the center of the conic whose equation is x^2 + 2y^2  6x + 8y = 0 2.Which one of the following equations represents a hyperbola? 
MATH
a parabola passes via the points (1.5,1) and (3,5). given that the vertex lies on the line 7x+3y4=0,find the focus and the equation of the parabola 
College Algebra
Find the equation of the parabola y = ax2 + bx + c that passes through the points. To verify your result, use a graphing utility to plot the points and graph the parabola. (−2, −15), (−1, −4), (1/2,10) y=? 
geometry
a parabola whose axis is parallel to the y axis passess through the points {1,1), (2.2) and (1,5). Find the equation of the parabola 
Math
Write the equation of a parabola, in standard form, that goes through these points: (0, 3) (1, 4) (1, 6) ax^2 + bx + c = y a * 0^2+b*0+c = 3 a*1^2+b+1+c = 4 a*(1)^2+b(1)+c = 6 c = 3 a + b + c = 4 a – b + c = 6 a + b + 3 = 4 …